1992
DOI: 10.1115/1.2920938
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Material, Manufacturing, and Operating Variables on the Friction Coefficient in OCTG Connections

Abstract: Results are presented from an experimental study conducted to determine friction coefficient behavior in OCTG connections. The study was conducted using the OCTG friction and galling tester at Texas Tech University. The tester employs tubular pin and box specimen pairs fabricated from 73-mm (2 7/8 in.) diameter OCTG tubing. Friction coefficient was determined for test specimens made of material grades L80 and J55 at loads of up to 620 kN (140,000 lb) acting on a surface area of up to 645 mm2 (1 in.2) with slid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 0 publications
5
12
0
Order By: Relevance
“…On the whole, the friction coefficient values from the block-on-ring tests present similar patterns for all compounds evaluated. This is consistent with a study already developed by Carper et al [9] with pin-on-box tests where little difference in friction performance between API Modified thread compound and a nonmetal-containing compound is shown. In Figure 8 (left) a typical set of results for a charge stroke of a block-on-ring test is presented.…”
Section: Friction Behaviorsupporting
confidence: 93%
See 3 more Smart Citations
“…On the whole, the friction coefficient values from the block-on-ring tests present similar patterns for all compounds evaluated. This is consistent with a study already developed by Carper et al [9] with pin-on-box tests where little difference in friction performance between API Modified thread compound and a nonmetal-containing compound is shown. In Figure 8 (left) a typical set of results for a charge stroke of a block-on-ring test is presented.…”
Section: Friction Behaviorsupporting
confidence: 93%
“…This behavior is typical of boundary lubrication regime. Although the friction evolution is similar to that obtained by Carper et al [14] in rotating pin-on-box tests lubricated with API Modified thread compound, the friction coefficient results obtained in this study are slightly higher than those reported by [15] for the range of contact pressure evaluated in the current tests. Also, from the graph in Figure 8 (left) it can be seen that a marked decrease in the COF value with the completion of the ring revolutions is noted after 5.2 s and 10.4 s. This is in line with the running-in phenomenon where the friction decreases when the surface asperities become burnished.…”
Section: Friction Behaviorsupporting
confidence: 80%
See 2 more Smart Citations
“…The axial displacements of all nodes are zero on the middle symmetry plane of the coupling, and their radial displacements are free. The friction coefficient of the thread interface is commonly in the range 0.016-0.026 [10] when the interface makes use of thread grease. The FEA mesh is shown in Fig.…”
Section: Finite Element Modelsmentioning
confidence: 99%